Sales Promotion and Pricing Strategy in Nigerian Telecommunications Companies - Aribaba, F. O.; Ahmodu, A. O.; Egbewole, I K.; Olayiwola, P. O.; Ajayi, J. O.; Lawal, N. A. (NIU Journal of Social Sciences, 2024)
The study examines the sales promotion and pricing strategies employed by MTN and Globacom, two prominent telecommunication companies in Nigeria. A quantitative research design was exploited for this study. The research population consists of the estimated 226.84 million subscribers, as reported by the Nigerian Communications Commission in 2023. A sample size of 384 respondents was selected using purposive and quota sampling techniques. The instrument underwent validation, and the reliability test conducted through Cronbach’s alpha yielded a coefficient of 0.964, indicating high reliability. Descriptive and inferential statistics were utilized to analyze the data. The descriptive analysis was bar chart while the analysis of variance (ANOVA) was employed to examine the significant association between the dependent variable and the independent variables. The statistical tool employed was SPSS version 20.0. The study’s results displayed the relationship between sales promotion and pricing strategies employed by MTN and Globacom telecommunication companies in Nigeria. These findings indicate a notable correlation between these vital components of business activities. Thus, the study suggests that MTN and Globacom should enrich their sales promotion strategies. It was recommended that regular valuateons guarantee the alignment with long-term goals, customer preferences, and current market trends. Keywords: Sales, Promotion, Pricing Strategy and Telecommunication